Bihar Second Five-Year Plan Progress Report for the Period Ending September, 1957 - Planning Commission (Planning Commission, 1957)
Abstract of Expenditure Scheme wise Progress Agricultural Production Minor Irrigation Soil Conservation Land Development Marketing Animal Husbandry Dairying and Milk Supply Forest.
Bihar